Implementation of Port Acceptance Facilities: Study at Tanjung Priok Port - Vidya Selasdini; Nafi Almuzani (Journal of Accounting and Finance Management, 2022)
The Marine Environment Protection Committee (MEPC), the 74th Session held on May 13-17, 2019, has highlighted several agendas, such as air pollution and energy efficiency. The draft guide to Port State Control (PSC) on contingency measures to address non-compliant fuel oil provides more details on managing the fuel still on board after the final fuel oil non-availability report (FONAR). Tanjung Priok Port is the largest and most complete port in Indonesia and is expected to provide reception facilities to support its implementation. The reception facilities owned by Tanjung Priok Port consist of tugboats, barges, separator pumps, and storage tanks. Most of these facilities are considered sufficient to provide and serve the needs of ships, especially those that need the appropriate fuel oil to come to the port. However, there is a potential shortage of reception facility services. This study aims to determine the availability and adequacy of port reception facilities in Tanjung Priok to formulate strategies to overcome non-compliant oil implementation. Field studies and surveys of respondents were conducted for data collection. Gap analysis is used to compare perceptions and expectations of the performance of port revenue facilities. The survey instrument consists of legality, equipment, infrastructure, and human resources aspects.